Bixin Protects Against Kidney Interstitial Fibrosis Through Promoting STAT6 Degradation - Li, Jianzhong; Yang, Youjing; Wei, Shuhui; Chen, Ling; Xue, Lian; Tian, Hailin; Tao, Shasha (Frontiers in Cell and Developmental Biology, 2020)
Bixin, a natural carotenoid extracted from the seeds of Bixa orellana, has anti-oxidant and anti-inflammation effects. However, the pharmacological effects and underlying mechanisms of bixin in kidney interstitial fibrosis remains unknown. Partial epithelial-to-mesenchymal transition (EMT) of tubular cells has been linked to renal interstitial fibrosis. Here, we found that in the unilateral ureteral obstruction model, bixin administration could ameliorate kidney interstitial fibrosis. The expression of signal transducer and activator of transcription 6 (STAT6) was dramatically increased in renal tubular cells. Bixin treatment inhibited STAT6 induction. The activation of STAT6 signaling was essential for transforming growth factor-beta1, fibrotic markers and EMT related proteins expression in HK2 cells, which was confirmed by using the Stat6-/- mice. Ubiquitination, but not the acetylation level of STAT6 was induced by bixin treatment and promote the suppression of phosphorylation and stability of STAT6. P62-dependent autophagy might be involved in this process. The study demonstrated that bixin can be exploited therapeutically to alleviate renal interstitial fibrosis by targeting STAT6 signaling deactivation.